2022
DOI: 10.1186/s41043-022-00308-8
|View full text |Cite
|
Sign up to set email alerts
|

Time to readmission and associated factors after post treatment discharge of severe acute malnourished under-five children in Pawe General Hospital

Abstract: Background Relapse or repeated episodes is the admission of a child with the diagnosis of severe acute malnutrition (SAM) after being discharged to a status of treated and cured from a stabilizing center. A child may experience more than one episode of SAM depending on the improvement of the underlying comorbidity. Thus, this study aimed to estimate the time to readmission of SAM and associated factors for under-five children in North West Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
3
5
0
1
Order By: Relevance
“…Furthermore, other studies have shown that most children admitted to the hospital were less than 1 year old [11,12]. In line with our results, studies conducted by Cohen, et al [9] and Kebede [26] also found a higher proportion of female children than males, constituting 43% and 56%, respectively, with a higher proportion of children residing in rural areas [26].…”
Section: Socio-economic and Demographic Characteristics Of The Childrensupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, other studies have shown that most children admitted to the hospital were less than 1 year old [11,12]. In line with our results, studies conducted by Cohen, et al [9] and Kebede [26] also found a higher proportion of female children than males, constituting 43% and 56%, respectively, with a higher proportion of children residing in rural areas [26].…”
Section: Socio-economic and Demographic Characteristics Of The Childrensupporting
confidence: 92%
“…They resided in rural areas and were predominantly female. Similar to our findings, previous studies on hospital admissions among children have consistently shown that the majority of admitted children are below 24 months of age [9,26,27]. Furthermore, other studies have shown that most children admitted to the hospital were less than 1 year old [11,12].…”
Section: Socio-economic and Demographic Characteristics Of The Childrensupporting
confidence: 92%
“…Globally, in 2018, one in twelve of the estimated 52 million children under five had acute malnutrition, and 2⋅9 million of these children were admitted for ready-to-use therapeutic feeding (RUTF) ( 7 ) . This might be due to loss to follow-up or attrition of caregivers from the centre after starting the treatment ( 8 ) . Whereas attrition is the interruption or defaulting before reaching the target weight for at least two consecutive weeks and it is a composite term of defaulted and self-discharged cases ( 3 , 9 , 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a remarkable variation is observed in attrition rates ranging as high as 1⋅67 % ( 17 ) to 25⋅2 % ( 18 ) . This might be associated with the increased intention of self-discharging at thetime of caregiver from the treatment centre before reaching the reference weight of the child with or without treatment progression ( 8 , 19 ) .…”
Section: Introductionmentioning
confidence: 99%
“…According to international Sphere standards, there are three main exit criteria for inpatient treatment of complicated SAM including cured, attrition, and death [ 6 , 10 ]. However, previous study finding indicated that about 20% to 36% self-discharged after treatment initiated was responsible for incidence of 1.2% to 10.4% re-admission of cases [ 3 , 4 , 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%